Virus Content and Growth Patterns of Callus Cultured in vitro from Healthy and Virus-Infected Citrus Species - Durán-Vila, Núria; Cambra, Mariano; Pina, José A.; Ballester-Olmos, José F.; Navarro, Luis (IOCV, 2021)
Stem segments from healthy and virus-infected Pineapple sweet orange, Mexican lime and Etrog citron were cultured on callus-inducing medium. Explants infected with citrus infectious variegation virus (CIVV), psorosis, vein enation and cachexia produced significantly less primary callus than healthy controls, whereas citrus tristeza virus (CTV) did not affect callus production. The growth of secondary callus during subculturing was similar in healthy and infected tissues. Indexing of callus indicated that the number of calli infected with CTV and vein enation decreased drastically with subculturing, whereas the number of calli infected with CIVV and psorosis did not decrease after five subcultures.